Recent Developments in Data Science and Intelligent Analysis of Information Proceedings of the XVIII International Conference on Data Science and Intelligent Analysis of Information, June 4–7, 2018, Kyiv, Ukraine - Chertov, Oleg; Mylovanov, Tymofiy; Kondratenko, Yuriy; Kacprzyk, Janusz; Kreinovich, Vladik; Stefanuk, Vadim (Advances in Intelligent Systems and Computing, 2019)
XVI, 384 p. 107 illus.